Про операторні включення у банахових просторах із щільно визначеними операторами - Melnik, V. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
With using the developed approaches [1], new results concerning the solvability and solution features of operator inclusions with densely defined and L-pseudomonotonous operators in reflexive Banach spaces have been obtained.